2012
DOI: 10.1037/a0025523
|View full text |Cite
|
Sign up to set email alerts
|

Problem-solving appraisal, gender role conflict, help-seeking behavior, and psychological distress among men who are homeless.

Abstract: Men who are homeless experience pervasive psychological stressors that diminish their capacity to cope and navigate life problems. Yet some of these men possess skills, self-perceptions, and attitudes that allow them to survive. This study examined the contribution of gender role conflict, attitudes toward seeking professional help, psychological distress, and problem-solving appraisal among 126 men who are homeless. The results suggest that participants who reported higher gender role conflict scores, especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 65 publications
0
10
0
1
Order By: Relevance
“…Men who have sex with men (MSM), homeless individuals, and those with a substance use disorder all demonstrate increased levels of psychological distress when compared to other populations (Herrell et al, 1999; Cochran and Mays 2000a; Cochran and Mays 2000b; Sandfort, de Graff, Bijl, and Schnabel, 2001; Slade, Grove, and Burgess 2011; Nguyen, Liu, Hernandez, and Stinson 2012). Psychological distress has been associated with both initiation of and relapse into substance use (Castellani, Wedgeworth, Wootton, & Rugle, 1997; Daughters, Lejuez, Kahler, Strong, & Brown, 2005; Laudet, Becker, & White, 2009; Hassel, Nordfjærn, and Hagen 2013) making improved psychological health an important goal for interventions promoting substance abstinence.…”
Section: Introductionmentioning
confidence: 99%
“…Men who have sex with men (MSM), homeless individuals, and those with a substance use disorder all demonstrate increased levels of psychological distress when compared to other populations (Herrell et al, 1999; Cochran and Mays 2000a; Cochran and Mays 2000b; Sandfort, de Graff, Bijl, and Schnabel, 2001; Slade, Grove, and Burgess 2011; Nguyen, Liu, Hernandez, and Stinson 2012). Psychological distress has been associated with both initiation of and relapse into substance use (Castellani, Wedgeworth, Wootton, & Rugle, 1997; Daughters, Lejuez, Kahler, Strong, & Brown, 2005; Laudet, Becker, & White, 2009; Hassel, Nordfjærn, and Hagen 2013) making improved psychological health an important goal for interventions promoting substance abstinence.…”
Section: Introductionmentioning
confidence: 99%
“…Even under this situation, problem-solving skills could certainly be helpful in locating resources, applying for government assistance, avoiding high-risk situations, and finding employment. Problem-solving in the homeless population has not been studied extensively; however, one study was designed to examine the relationship between help-seeking attitudes, problem-solving appraisal, masculinity, and psychological distress among homeless men living at a transitional shelter (Nguyen, Ming Liu, Hernandez, & Stinson, 2012). It was conducted with 126 homeless men and involved assessment through a problem-solving inventory, along with other measures not directly relevant to problem-solving.…”
mentioning
confidence: 99%
“…However, these traits are sometimes maladaptive and unhealthy. Research has shown that males who do endorse such characteristics do not tend to utilize psychological services and are typically unaware of their own intrapersonal levels of distress or symptoms of ill health (Nguyen, Ming Liu, Hernandez, & Stinson, 2012). It may be important to further examine how gender role socialization and masculinity impact mental health and help-seeking behaviors.…”
Section: Masculinitymentioning
confidence: 99%
“…The process also requires vulnerability. Therefore, mental health services may be disagreeable for some men (Nguyen et al, 2012). Yousaf, Popat, and Hunter (2014) indicated that men endorse more reluctant attitudes towards seeking help for mental health and psychological difficulties.…”
Section: Masculinitymentioning
confidence: 99%
See 1 more Smart Citation